Red, Blue, or Purple Produce?: Exploring Liberalism, Conservatism and the Politics of Midwest Farmers' Market Participants - Davey, Andrew (My University, 2011)
"Really? Conservatives like farmers' markets?" This was one of the most common responses I heard when telling friends, colleagues, or strangers about my research on what motivates people from different political positions to participate in farmers' markets. The summer I did my field work for this project I was also working at Troy Community Farm in Madison, WI, a 5 acre urban vegetable farm that sold part of its produce at a neighborhood farmers' market. Most of the people I worked with were liberal or left-leaning politically, and I remember very vividly one day giving my research "elevator speech" to a fellow worker while we methodically plodded through the muddy rows, hunched over, rhythmically picking beans. When I told her I talked to several conservatives who supported farmers' markets and were very concerned about the environmental impacts of farming and the dominance of large agri-business corporations, she stopped dead in her tracks, stood up, turned around and looked at me with wide eyes in complete disbelief. Another common response was to laugh because my conversant thought I was joking. On one occasion, just before I started field work, I was talking to a graduate student who became rather intrigued when I said my research was about the politics of the farmers' market. When I told him, however, that I was planning to interview conservatives at various Midwest farmers' markets he chuckled, assuming I was being facetious because I wouldn't find anyone to interview. Then he started to verbally craft a derisively absurd imaginary market, something akin to conservatives in business suits sitting behind booths full of butternut squash and fresh picked flowers; he was grinning sardonically the whole time until he realized I wasn't smiling and I was serious about my research project.
Includes bibliography.
Keywords: Politics; Midwest; Farmers markets